2023
DOI: 10.1021/acsami.3c09652
|View full text |Cite
|
Sign up to set email alerts
|

2,2′-Azobis(1,5′-bitetrazole) with a N10 Chain and 1,5′-Bitetrazolate-2N-oxides: Construction of Highly Energetic Nitrogen-Rich Materials Based on C–N-Linked Tetrazoles

Ze Xu,
Tianyang Hou,
Feng Yang
et al.

Abstract: A series of high-nitrogen compounds, including a unique molecule 2,2′-azobis(1,5′-bitetrazole) with a branched N 10 chain and 1,5′-bitetrazolate-2N-oxides, were synthesized successfully based on C−N-linked 1,5′-bistetrazoles using azo coupling of N-amine bonds and N-oxide introduction strategies. All compounds were characterized by NMR spectroscopy, IR spectroscopy, elemental analysis, and differential scanning calorimetry, in which the structures of five compounds were further determined by single-crystal X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Then, an aqueous solution of 1,5′-bistetrazole was oxidized with potassium peroxymonopersulfatem (Oxone) at 40 °C for 3 days. The pH of the reaction solution was adjusted to 4–5 by adding an appropriate amount of acid, and the oxidation product obtained was HBTNO ( 1 , yield: 56%).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, an aqueous solution of 1,5′-bistetrazole was oxidized with potassium peroxymonopersulfatem (Oxone) at 40 °C for 3 days. The pH of the reaction solution was adjusted to 4–5 by adding an appropriate amount of acid, and the oxidation product obtained was HBTNO ( 1 , yield: 56%).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In our recent study, we reported a 1,5′-bitetrazolate-2 N -oxide (HBTNO) with two tetrazole rings, which has an excellent nitrogen–oxygen content, high energy density, and good stability . Based on these promising characteristics, we further explored the synthesis of EMOFs using Cu­(II), Co­(II), Zn­(II), and Ag­(I) (EMOFs 2 – 5 ) in combination with BTNO – anions.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-energy properties often frequently give rise to diminished stability. Tetrazole is the ideal candidate for balancing “energy and stability” among nitrogen-rich heterocyclic compounds because of its high nitrogen content, enthalpy of formation, and tendency toward lower sensitivity. , Polycyclic tetrazoles have gained significant attention in recent years due to their higher nitrogen content and energy potential. …”
Section: Introductionmentioning
confidence: 99%
“…Various synthetic strategies have been described for creating new energetic materials, such as the introduction of ring and cage strain, or aiming to reach the highest possible nitrogen content. [5][6][7][8] In order to achieve these properties in a compound, the same energetic building blocks are often used. [1][2] Well-known examples are functionalization with nitro, nitrato, nitrimino and nitramino groups, or the addition of covalent azides.…”
Section: Introductionmentioning
confidence: 99%